Study the Electrical Insulation of Polymeric Composite - Jaffer, Harith I; Harair, Remonda; Ammar, Noura; Mahdi, Yousra; Noaman, Riyadh (Al-Nahrain Journal of Science, 2018)
Electrical insulators in this research were made from reinforced epoxy with three kinds of fiberglass (wool, low surface density and high surface density). Samples made manually, resistivity, insulation voltage, tensile strength and bending test were done. The results showed that the highest tensile strength for reinforced epoxy with low surface density fiberglass was (195 N/mm2), while highest bending stress was for reinforced epoxy with high surface density fiberglass (84 N/mm2). Mechanical properties test was done for samples to ensure that they can be used as replacement of ceramic insulators (porcelain) which is used as insulators in transformer, cabins manufacturing and as electrical wiring’s load which transmitter for electrical current. Reinforced epoxy with wool fiberglass has highest resistivity (28.4*10+1Ω cm) and increasing in insulation voltage for reinforced epoxy with high surface density fiberglass (30 kv).